2008
DOI: 10.1021/jo802392c
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric 1,3-Dipolar Cycloaddition Reactions of Nitrile Oxides Catalyzed by Chiral Binaphthyldiimine-Ni(II) Complexes

Abstract: Asymmetric cycloaddition reactions between several nitrile oxides and 3-(2-alkenoyl)-2-oxazolidinones and 2-(2-alkenoyl)-3-pyrazolidinone derivatives were carried out in the presence of chiral binaphthyldiimine (BINIM)-Ni(II) complexes as catalysts. Using (R)-BINIM-4(3,5-xylyl)-2QN-Ni(II) complex (30 mol %), good regioselectivity (4-Me/5-Me = 85:15) along with high enantioselectivity (96% ee) of the 4-Me adduct were obtained for the reaction between isolable 2,4,6-trimethylbenzonitrile oxide and 3-crotonoyl-5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…89 Recently, Suga and coworkers have disclosed a novel synthetic protocol featuring BINIM-Ni(II) complexes as chiral Lewis acid catalysts for the asymmetric cycloadditions of nitrile oxide (Scheme 87). 90 The nitrile oxides were generated from the corresponding hydroximoyl chloride 166 in the presence of MS 4 Å. The best result, in terms of enantioselectivity (96% ee), was achieved for the reaction of isolable 2,4,6-trimethylbenzonitrile oxide 167 and 3-crotonoyl-5,5-dimethyl-2-oxazolidinone 168a as the dipolarophile.…”
Section: Catalytic Asymmetric 13-dipolar Cycloadditions Of Nitrile Omentioning
confidence: 99%
“…89 Recently, Suga and coworkers have disclosed a novel synthetic protocol featuring BINIM-Ni(II) complexes as chiral Lewis acid catalysts for the asymmetric cycloadditions of nitrile oxide (Scheme 87). 90 The nitrile oxides were generated from the corresponding hydroximoyl chloride 166 in the presence of MS 4 Å. The best result, in terms of enantioselectivity (96% ee), was achieved for the reaction of isolable 2,4,6-trimethylbenzonitrile oxide 167 and 3-crotonoyl-5,5-dimethyl-2-oxazolidinone 168a as the dipolarophile.…”
Section: Catalytic Asymmetric 13-dipolar Cycloadditions Of Nitrile Omentioning
confidence: 99%
“…A major limitation that remains to the uses of nitrones in cycloaddition reactions is access to C-alkyl nitrones and reactivity/selectivity with those that are ketone derivatives. Dipolar cycloaddition reactions of nitrile oxides have received far less attention than those of nitrones [111][112][113]. By using a chiral N,N 0 -dioxideÀnickel (II) complex as a catalyst, good regioselectivities and excellent enantioselectivities were obtained in the 1,3-dipolar cycloaddition reaction of nitrile oxides with 3-arylidene-oxindoles (Scheme 23) [102].…”
Section: Nitrones and Nitrile Oxidesmentioning
confidence: 99%
“…Slow addition of the dipole was essential for obtaining higher enantioselectivities. Enantiomeric excess of up to 93% was achieved when 4-trifluoromethyl benzonitrile oxide was used as the dipole at -20 ºC ( Suga et al [64] have recently reported nitrile oxide cycloaddition to electron deficient olefins using a chiral nickel catalyst. The nitrile oxide was generated in situ by the dehydration of corresponding hydroximoyl chloride using molecular sieves.…”
Section: Lewis Acid Mediated Nitrile Oxide Cycloaddition Reactionsmentioning
confidence: 99%